Dynamic analysis of floating bridges - Papinutti, Mitja (visokošolska dela, 2021)
The floating bridge is an ambitious structure that enables new long-span sea crossings. Floating structures are susceptible to dynamics due to their slender structures and interactions with the surrounding environment. The dynamic response can govern the floating bridge design; therefore, an accurate and representative dynamics model is crucial. This thesis provides a comprehensive overview of all the relevant environmental loads, such as turbulent wind loads, self-excited wind loads, wave radiation loads, wave loads, and viscous drag damping currents. All modeling is suited for a time-domain integration method that successfully calculates the nonlinear correlated bridge response. Different state-of-the-art wind self-excited modeling techniques are presented, such as the quasi-steady state and flutter derivative techniques. The scientific contribution is a new velocity convolution of the flutter derivative model based on the theory of linear flutter derivatives. The proposed models are designed to be successfully introduced into various commercial codes, thus allowing more integrative wind designs in practice. The newly developed models are also experimentally validated in the Norwegian University of Science and Technology wind tunnel.
Keywords: bridge dynamics; Built Environment; civil engineering; current loads; časovna integracija odziva; dimenzioniranje plavajočih mostov; dinamika mostov; Disertacije; doctoral thesis; floating bridge design; flutter derivatives; gradbeništvo; Grajeno okolje; obtežba morskih tokov; obtežba valov; odvodi omahovanja; Plavajoči mostovi; time integration; vetrna analiza; wave loads; wind analyses